The visibility of black people with disabilities nudity: for an anticapacitist aesthetic (Revista de Ensino em Artes, Moda e Design, 2023)
Societies are now based on the effects of control devices, within which are normalizing ideals of such societies. These ideals built a structural binarism: on the one hand, the healthy, the efficient, the perfect, the beautiful and the white; on the other, the sick, the handicapped, the imperfect, the ugly and the black. It is within this binarism that an ableist aesthetic is fostered, imposing on the bodies of disabled people, especially the disabled black population, a dense obscurity, preventing these bodies from being thought from an aesthetic perspective. This article aims to think about the “place” of the bodies of black people with disabilities in our societies, especially in artistic manifestations, while uncovering ways that enable the visibility of these bodies, capable of inaugurating an anti-ableism aesthetic.
Keywords: normalizing societies; disabled; visual arts; ableism; anti-ableism